'Collectivism' and 'assertiveness' as determinants of innovation in small and medium enterprises in Egypt. (2017) - Badawy, Tarek A. El; Chinta, Ravi; Magdy, Mariam M.
Hofstede's metrics of national culture have been extensively studied in a wide variety of organisational settings since his seminal work in 1983. However, there is a paucity of research on the effects of Hofstede's culture metrics on firm innovation in small and medium enterprises in Egypt. This study empirically investigates the main and interaction effects of two of Hofstede's cultural metrics on firm innovation in small and medium enterprises in Egypt. The results from a survey of 326 respondents in small and medium enterprises in Egypt reveal that though the main effects of collectivism and assertiveness are not statistically significant as expected from extant literature, the interaction effect between the two is strong and statistically significant. Results are justified through the resonance effect that stems from two weak forces. Further implications of the findings are discussed. The study is concluded with practical implications for managers, policy makers and for future research endeavours.